Designing a Lecture Journal Information System as an Effort to Monitor and Evaluate the Learning Process (Literature Study) - Hamsy, Annisa; Ritonga, Irma; Elfrianto, Elfrianto (Indonesian Journal Education, 2024)
In the learning process, it is necessary to hold a monitoring process to see the extent of the lecture activities that have been carried out. Lecture journal documents contain material delivered by lecturers to students at each lecture meeting which aims for information and data on the lecture process. This research aims to design an information system for monitoring and evaluating the learning process which is expected to be able to provide solutions in monitoring and evaluating learning activities that are transparent, accountable and realtime. The method used in this research is literature study. The conclusion in this study is that the information system for monitoring and evaluating the learning process has very important benefits for making decisions in the teaching and learning process in the future